2018
DOI: 10.1371/journal.pone.0202412
|View full text |Cite
|
Sign up to set email alerts
|

Perceived neighbourhood affluence, mental health and wellbeing influence judgements of threat and trust on our streets: An urban walking study

Abstract: This study aimed to understand how people respond to different urban neighbourhoods. We explored whether participants’ mental health and wellbeing, judgements of resident wealth, family SES and sentiments reflected in descriptions of place features predicted in situ sense of threat and trust. Forty-six student participants walked in groups through 2 urban neighbourhoods, separated by a park, in the North West of England, noting responses at pre-determined stops. Significant differences existed in participants’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…It therefore appears that the effect of the neighborhood environment on mental-health operates as a function of overall deprivation, with associations between neighborhood components and mental-health symptoms becoming increasingly relevant as deprivation increases. This finding supports the idea of a tipping point whereby neighborhood environments that accrue too many negative characteristics (e.g., social disorder, low cohesion) begin to affect the mental health of inhabitants (Corcoran et al, 2018). The identification of where this tipping point might be and of how neighborhood characteristics and notions of social cohesion are emotionally weighted to determine their contribution to overall environmental stress (shown here in expressions of anxiety and paranoia) are clear areas for further research.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It therefore appears that the effect of the neighborhood environment on mental-health operates as a function of overall deprivation, with associations between neighborhood components and mental-health symptoms becoming increasingly relevant as deprivation increases. This finding supports the idea of a tipping point whereby neighborhood environments that accrue too many negative characteristics (e.g., social disorder, low cohesion) begin to affect the mental health of inhabitants (Corcoran et al, 2018). The identification of where this tipping point might be and of how neighborhood characteristics and notions of social cohesion are emotionally weighted to determine their contribution to overall environmental stress (shown here in expressions of anxiety and paranoia) are clear areas for further research.…”
Section: Discussionsupporting
confidence: 82%
“…In a recent study by Corcoran et al (2018) using experience sampling methodology, it was shown that in situ judgments of neighborhood trust were strongly predicted by judgments of residents’ wealth and the participants’ baseline levels of paranoid ideation. In the same study, level of threat felt by the participants as they walked through a deprived neighborhood was significantly and independently predicted by self-reported personal resilience of the participants after controlling for other correlates such as family socioeconomic status (SES), weather, depression, anxiety, and baseline paranoia.…”
Section: The Neighborhood Social Environment: the Impact Of Deprivationmentioning
confidence: 99%
“…This may provide a much more fine-grained insight into how the effects of urban stressors identified in epidemiological studies depend on specific contexts (Söderström et al, 2016). Corcoran et al (2018) collected data on walkers' in situ judgements of threat and trust in two urban neighbourhoods, which differed in terms of deprivation. Perceptions of trust and threat were influenced by the perception of neighbourhood affluence, but also by the mental health and wellbeing of the walkers.…”
Section: Experimental and Experience-based Studies -Testing Causalitymentioning
confidence: 99%
“…Corcoran et al (2018) collected data on walkers' in situ judgements of threat and trust in two urban neighbourhoods, which differed in terms of deprivation. Perceptions of trust and threat were influenced by the perception of neighbourhood affluence, but also by the mental health and wellbeing of the walkers.…”
Section: Introductionmentioning
confidence: 99%
“…personal health, financial status) are more robustly associated with subjective wellbeing than community or place characteristics [ 11 ], others suggest that individual, community and place characteristics should not be considered independently from one another. This is because they likely operate in a complex system of reciprocal relationships [ 12 ] as can be shown in research using mobile data collection methods for example [ 13 ]. It is incontrovertible that one’s relative flourishing or languishing will depend, at least in part, on what resources we have available to us in our neighbourhoods and communities.…”
Section: Introductionmentioning
confidence: 99%